Does adoption of the rice–crayfish co-culture model improve farmers’ income? - Xingjie Yang; Zhenhong Qi (PLoS ONE, 2025)
This study empirically assesses the income effects of the rice–crayfish co-culture model using endogenous switching regression (ESR) and mediation models, based on survey data from 1,058 farm households in Hubei Province. Key findings reveal that adoption of the rice–crayfish co-culture model significantly boosts farmers’ total income: counterfactual analysis shows non-adopters would experience a 22.423% decline in average household income if they ceased adoption. The adoption of the rice–crayfish co-culture model differential impacts on the income of various farmer groups. This divergence primarily stems from the model’s significantly stronger positive effect on agricultural income compared to its minimal dampening effect on non-farm income. By examining the mechanism of its effect on farmers’ income, we find that adopting the rice–crayfish co-culture model mainly promotes farmers’ income by affecting the human capital of the family. Based on the above conclusions, the Chinese government should further promote the sustainable development of the rice–crayfish co-culture model and give full play to its role in increasing farmers’ income. Simultaneously, constructing a comprehensive industrial system for the rice–crayfish co-culture model and intensifying technical training are imperative. These efforts aim to enhance the human capital of farmers, which in turn will effectively promote the growth of their income.